Hepatitis B Surface Antigen (HbsAg) Prevalence and Risk Factors in Women of Childbearing Age in Eastern Algeria - Amel Ouyahia; Mounira Rais; Aya Kouicem; Mohamed Kouicem; Meriem Abdoun; Slimane Laouamri (Clinical and Research Journal in Internal Medicine, 2023)
Background: Hepatitis B is the most common chronic viral infection and a significant contributor to morbidity and death globally. Based on the mother's hepatitis B e antigen (HBeAg) status, the probability of perinatal HBV infection in children delivered to mothers with HBV ranges from 10% to 85%.Aim: to determine the prevalence of hepatitis B virus infection among women of childbearing age in the eastern region of Algeria and investigate risk factors for infection to recommend ways to reduce the disease's impact on neonatal morbidity and mortality.Methods: We conducted a cross-sectional study in Sétif, Algeria, from 2005 to 2007 to assess the prevalence of Hepatitis B Surface Antigen among women of childbearing age. This study is the first and only one in Algeria. Data on risk factors, obstetrics, and sociodemographic were gathered using structured questionnaire; they were subsequently tested using an enzymelinked immunosorbent assay for HBsAg. The data collected were entered and processed using Epi info 3.3.2 software. Infection prevalence, sociodemographic, clinical, obstetric and risk factors variable frequency distributions were calculated. The student's t-test and Fisher's exact test were applied, at a significance level of 5%.Results: There are834 women of childbearing age's medical records were examined for this study. 1% of HBsAg test findings were positive. Positive HBsAg didn't significantly correlate with any other variables, including age, place of residence, municipality, marital status, occupation, parity, current pregnancy, reason for current consultation, transmission risk factors (blood transfusion, recent piercing, dental care, shared personal hygiene equipment, injection with multiple use equipment, tattoo, scarification, partner characteristics). However, history of jaundice has a significant protective effect against HBsAg positive.Conclusion: Although our results classify the two municipalities studied as low prevalence areas (< 2%). Prenatal HBsAg screening is strongly advised.